Panela de Mão, the Brazilian Handpan: an artistic perspective based on two marches composed by Chiquinha Gonzaga and adapted for the Duo Piano & Panela - Reznik, Felipe; Madeira, Maria Teresa (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
The popular instrument known as handpan was created in the year 2000 in Switzerland, originally called hang. In its short life story, the instrument had a lot of names and one of them was hang drum. However, the creators prohibited the drum in its identification. Considering this context, the following article presents panela de mão. Not only a translation to the Portuguese language, but a decolonial rescue of the drum to the instrument. As the artistic proposal of the development of the Brazilian handpan, two marches composed by Chiquinha Gonzaga were used as an example of the vast technical and artistic possibilities given by this instrument. The Duo Piano & Panela, formed by Reznik and Madeira, is an artistic result of this search that presents unprecedented arrangements to this formation.